Promoting health in the Babylon Governorate: public awareness regarding a healthier lifestyle - Watife, Abeer T.; Abdulameer, Noor Anwer; Alzubaidi, Fatima Adnan; Abdul-Husseein, Hajir Karim; Al-Shuaibi, Hiba F.; Jubouri, Fatima M. Al; Owadh, Hasanain K. Hasan (Pharmakeftiki, 2025)
This study explores public awareness of healthy lifestyle practices in the Babylon Governorate (Iraq), with a particular focus on Hillah city and its surrounding districts. The research investigates perceptions and engagement in behaviours that promote well-being and mitigate the risk of chronic disease. Data were collected from 391 participants between December 23, 2022, and February 9, 2023. Socio-demographic variation was minimal, except in relation to marital status, age, body mass index (BMI), family size, and occupation. Notably, female participants demonstrated significantly greater familiarity with the concept of the food pyramid compared to their male counterparts (p<0.05). While many respondents reported adherence to healthy habits – such as adequate sleep, stress management, hydration, and general nutritional awareness – only a small proportion engaged in regular physical activity or consistently applied food pyramid principles to their dietary choices. This discrepancy suggests a gap between nutritional knowledge and actual dietary behavior. Overall, awareness of healthy living did not differ significantly between urban and rural populations within the Babylon Governorate.